COMPUTERIZED ROOM RENTAL FEE PAYMENT SYSTEM IN PURI MIRA - Muhamad Sarwono; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2003)
Lodging as an organization also requires computer facilities as needs and serviceswhich will generate information and reports are accurate and quick in processingservices. And reduced human error in finding the data.In this study the author conducted interviews and read books related to lodging.Based on the results of the discussion on scientific writing, the implementation ofcomputerization on the reservation is very helpful at all to face the problem of datasecurity more secure by using computerization as compared with the manual method,because the data is stored in a floppy or hard disk that is not easy to lost or damaged.In running the system procedure, the authors suggest to the user in order to alwaysmaintain the system and the data so well that the expected output is always up to date.